2006
DOI: 10.1089/acm.2006.12.65
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Pressure After Various Forms of Therapeutic Massage: A Preliminary Study

Abstract: Type of massage was the main factor affecting change in BP. Increases in BP were noted for potentially painful massage techniques, including trigger point therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 11 publications
3
25
0
2
Order By: Relevance
“…Some investigators found no significant effects of massage therapy on psychological responses (Cowen et al, 2006;Combron et al, 2006). However, findings of the present study are consistent with the studies conducted by Haji Hoseini et al, (2006) and Shaban et al (2004).…”
Section: Discussionsupporting
confidence: 92%
“…Some investigators found no significant effects of massage therapy on psychological responses (Cowen et al, 2006;Combron et al, 2006). However, findings of the present study are consistent with the studies conducted by Haji Hoseini et al, (2006) and Shaban et al (2004).…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Cambron et al (2006) six different massage techniques were used including Swedish (effleurage and petrissage), deep tissue, myofascial release, trigger point, sports and craniosacral massage. Massage ranged between 30-90min in duration.…”
Section: Combination Trials Focussing On Changes In Blood Flowmentioning
confidence: 99%
“…From the data released by Dishub komintel Aceh in the last three years, as many as 2,104 people died from road accidents. The number of traffic accidents in 2010 reached a total of 806 cases when 649 people died [7]. It increased in 2011 with a total number of 1,327 cases (up 64.64%), 732 people died (up 12.7%).…”
Section: Introductionmentioning
confidence: 99%